Aluminum fin material and method of manufacturing the same

JP2025023487APending Publication Date: 2025-02-17KOBE STEEL LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023127637
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

AI Technical Summary

Benefits of technology

【0012】 本発明に係るアルミニウム製フィン材は、非常に優れた耐食性を有する。そのため、耐食性皮膜層の皮膜量を従来よりも少なくしても十分な耐食性を実現できる。その結果、製造コストを下げること等ができる。 上記に加え、アルミニウム製フィン材が、空調機等の熱交換器に用いられる場合には、耐食性皮膜層の皮膜量を少なく、すなわち層厚みを薄くできることから、アルミニウム製フィン材に求められる熱伝導性や熱交換効率を阻害することなく、優れた耐食性をも両立したアルミニウム製フィン材を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023487000001
    Figure 2025023487000001
  • Figure 2025023487000002
    Figure 2025023487000002
Patent Text Reader

Abstract

To provide an aluminum fin material having very excellent corrosion resistance.SOLUTION: An aluminum fin material includes an aluminum plate, and a corrosion resistant film layer and a hydrophilic film layer provided in this order at least on one surface of the aluminum plate, wherein the corrosion resistant film layer contains epoxy resin and silicone containing an epoxy group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum fin material and a manufacturing method thereof. [Background technology]

[0002] Heat exchangers are used in products in various fields, such as room air conditioners, packaged air conditioners, freezer showcases, refrigerators, oil coolers, and radiators. Aluminum and aluminum alloys, which have excellent thermal conductivity, workability, and corrosion resistance, are generally used as materials for heat exchanger fins. Plate fin and plate and tube heat exchangers have a structure in which aluminum fin materials are arranged in parallel at close intervals.

[0003] When the aluminum fin material of the heat exchanger is in cooling mode, the cooled refrigerant flows through the copper tubes, causing the surface temperature of the fin material to drop below the dew point. As a result, condensation water adheres to the surface of the fin material. The surface of the aluminum fin material is easily corroded by the effects of this condensation water.

[0004] The aluminum corrosion products produced by the above-mentioned corrosion can become adhesion sites for odorous components in the air, and various problems are of concern, such as water splashing due to the water repellency of the surface caused by the adhesion of water-repellent components, and the odor of the corrosion products themselves.

[0005] In response to this, Patent Documents 1 to 3 propose a technique of coating the surface of an aluminum plate with a water-repellent corrosion-resistant film layer in order to suppress corrosion of the aluminum plate. Specifically, Patent Documents 1 to 3 disclose a configuration in which a corrosion-resistant film containing a hydrophobic resin is provided between the aluminum plate and a hydrophilic film. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2021-162164 A [Patent Document 2] Patent Publication No. 2021-162165 [Patent Document 3] JP 2022-161706 A Summary of the Invention [Problem to be solved by the invention]

[0007] Although the provision of a corrosion-resistant coating layer can suppress corrosion of an aluminum plate, if the same or higher corrosion resistance could be achieved with a smaller amount of coating, it would lead to reduced manufacturing costs, etc. Therefore, a corrosion-resistant coating layer having higher corrosion resistance is desired.

[0008] Therefore, an object of the present invention is to provide an aluminum fin material having extremely excellent corrosion resistance and a manufacturing method thereof. [Means for solving the problem]

[0009] As a result of further investigations into the above-mentioned problems, the present inventors discovered that by incorporating a silicone containing an epoxy group in addition to the conventional epoxy-based resin in the corrosion-resistant coating layer, extremely excellent corrosion resistance could be achieved, which led to the completion of the present invention.

[0010] The present invention relates to the following [1] to [8]. [1] An aluminum plate having a corrosion-resistant coating layer and a hydrophilic coating layer in this order on at least one surface of the aluminum plate; The aluminum fin material, wherein the corrosion-resistant coating layer contains an epoxy resin and a silicone containing an epoxy group. [2] The aluminum fin material according to [1], wherein the content of the epoxy group-containing silicone in the corrosion-resistant coating layer is 0.1 to 20 mass %. [3] The coating amount of the corrosion-resistant coating layer is 0.1 to 20 mg / dm 2 The aluminum fin material according to [1] or [2] above. [4] The aluminum fin material according to any one of [1] to [3] above, wherein the hydrophilic coating layer contains an acrylic resin containing a sulfonic acid group and an ether bond. [5] The aluminum fin material according to any one of [1] to [4] above, further comprising a lubricating coating layer on the surface of the hydrophilic coating layer. [6] The aluminum fin material described in [5], wherein the lubricating coating layer comprises a resin matrix containing polyethylene glycol as a main component and a hydrophilic component containing at least one of a sulfonic acid group and an ester group. [7] The aluminum fin material according to any one of [1] to [6], further comprising a base treatment layer between the aluminum plate and the corrosion-resistant coating layer.

[0011] [8] A method for manufacturing an aluminum fin material comprising an aluminum plate and a corrosion-resistant coating layer and a hydrophilic coating layer in this order on at least one surface of the aluminum plate, A method for producing an aluminum fin material, comprising the steps of applying and dehydrating and condensing a coating composition containing an epoxy resin composition and at least one of silicon and a silane coupling agent having an epoxy group, to form the corrosion-resistant coating layer. Effect of the Invention

[0012] The aluminum fin material according to the present invention has very excellent corrosion resistance. Therefore, sufficient corrosion resistance can be achieved even if the amount of the corrosion-resistant coating layer is reduced compared to the conventional case. As a result, the manufacturing cost can be reduced. In addition to the above, when the aluminum fin material is used in a heat exchanger of an air conditioner or the like, the amount of the corrosion-resistant coating layer can be reduced, i.e., the layer thickness can be made thin, so that an aluminum fin material that combines excellent corrosion resistance without impairing the thermal conductivity and heat exchange efficiency required of the aluminum fin material can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the aluminum fin material according to the present invention will be described in detail. Note that the symbol "to" indicating a numerical range is used to mean that the numerical range includes the numerical ranges before and after the symbol as the lower and upper limits.

[0014] Aluminum fin material The aluminum fin material (hereinafter sometimes simply referred to as "fin material") of this embodiment comprises an aluminum plate and, on at least one surface of the aluminum plate, a corrosion-resistant coating layer and a hydrophilic coating layer, in that order.

[0015] <Corrosion-resistant coating layer> The corrosion-resistant coating layer in this embodiment contains an epoxy resin and a silicone containing an epoxy group. The fin material according to this embodiment has the above-mentioned corrosion-resistant coating layer between the aluminum plate and the hydrophilic coating layer, but when the fin material further has a base treatment layer, it is preferable to have the above-mentioned corrosion-resistant coating layer between the base treatment layer and the hydrophilic coating layer.

[0016] The corrosion-resistant coating layer is a layer for increasing the corrosion resistance of the aluminum plate, and prevents the penetration of moisture such as condensation water, oxygen, ions such as chloride ions, etc. into the aluminum plate, thereby suppressing the corrosion of the aluminum plate and the generation of aluminum oxides that cause odors. In addition, the corrosion-resistant coating layer can improve the adhesion between the aluminum plate and the hydrophilic coating layer, and can maintain the function of the hydrophilic coating layer for a longer period of time. As a result, in addition to the corrosion resistance of the corrosion-resistant coating layer, the film-forming property, the heat exchange efficiency of the fin material, and the hydrophilic function of the hydrophilic coating layer can be improved.

[0017] In contrast to the effects of the above-mentioned corrosion-resistant coating layer, the corrosion-resistant coating layer of this embodiment contains silicone containing an epoxy group in addition to the epoxy resin, thereby achieving extremely excellent corrosion resistance.

[0018] The reason for this is unclear, but we believe it is as follows. First, epoxy group-containing silicone is a polymeric compound obtained by polymerizing a silane compound having a main skeleton formed by siloxane bonds to which epoxy groups have been introduced. For example, this can be obtained by dehydration condensation of silicone having an epoxy group or a silane coupling agent having an epoxy group.

[0019] It is presumed that the presence of epoxy groups in the silicone precursors, such as silicone and silane coupling agents, increases the compatibility between the epoxy resin and the silicone or silane coupling agent, resulting in a highly homogeneous corrosion-resistant coating layer.

[0020] High homogeneity means that the epoxy resin and silicone do not separate and there is no clear interface between them. This high homogeneity of the corrosion-resistant coating layer prevents moisture and ion species that cause corrosion of the aluminum plate from passing through the corrosion-resistant coating layer and reaching the aluminum plate, which is believed to result in extremely excellent corrosion resistance.

[0021] The main skeleton of the epoxy group-containing silicone formed by siloxane bonds may be a linear siloxane skeleton or a cyclic siloxane skeleton, but from the viewpoint of ensuring uniform dispersibility in the coating material, a linear siloxane skeleton is preferred.

[0022] Specific examples of silicone having an epoxy group include KF series manufactured by Shin-Etsu Silicones Co., Ltd. and DOWSIL manufactured by Dow Toray.

[0023] Specific examples of silane coupling agents having an epoxy group include KBM series manufactured by Shin-Etsu Silicones Co., Ltd. and DOWSIL manufactured by Dow Toray Co., Ltd.

[0024] The content of the epoxy group-containing silicone in the corrosion-resistant coating layer in this embodiment is preferably 0.1 to 20% by mass. From the viewpoint of corrosion resistance, the content is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.5% by mass or more. From the viewpoint of hydrophilicity, the content is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0025] The epoxy resin in this embodiment is a resin that is crosslinked and cured by epoxy groups remaining in the polymer.

[0026] Examples of prepolymers of epoxy resins before curing include bisphenol A type, bisphenol F type, bisphenol S type, and halogen- or alkyl-substituted or hydrogenated products of these bisphenols. Examples of curing agents include polyamines, acid anhydrides, polyamides, and imidazoles.

[0027] Commercially available bisphenol A type epoxy resins include, for example, jER (registered trademark) 1001, 1002, 1003, 1004, 1004AF, 1005, 1006FS, 1007, 1009, and 1010 manufactured by Japan Epoxy Resins Co., Ltd., Epotohto (registered trademark) YD-011, YD-012, YD-013, YD-014, YD-017, YD-019, and YD-020G manufactured by Tohto Kasei Co., Ltd., and Epicron (registered trademark) 860, 1050, 1055, 3050, 4050, and 7050 manufactured by DIC Corporation. Commercially available brominated bisphenol A type epoxy resins include, for example, jER (registered trademark) 5046B80, 5047B75, 5050, 5050T60, and 5051 manufactured by Japan Epoxy Resins Co., Ltd., and Epiclon (registered trademark) 152 and 153 manufactured by DIC Corporation. Commercially available bisphenol F type epoxy resins include, for example, jER (registered trademark) 806, 807, 4002P, 4004P, 4007P, and 4009P manufactured by Japan Epoxy Resins Co., Ltd., and Epotohto (registered trademark) YDF-2001 and YDF-2004 manufactured by Tohto Kasei Co., Ltd. Commercially available bisphenol S type epoxy resins include, for example, Epiclon (registered trademark) EXA-1514 manufactured by DIC Corporation.

[0028] The content of the epoxy resin in the corrosion-resistant coating layer in this embodiment is preferably 80 to 99.9% by mass. From the viewpoint of hydrophilicity, the content is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. From the viewpoint of corrosion resistance, the content is preferably 99.9% by mass or less, more preferably 99.8% by mass or less, and even more preferably 99.5% by mass or less.

[0029] The corrosion-resistant film layer in this embodiment may contain other resins other than the epoxy resin. The other resins are preferably hydrophobic resins, such as polyolefin resins, acrylic resins, polyester resins, polyurethane resins, and melamine resins. These other resins may be contained in one type or in two or more types. The other resins are preferably water-dispersible.

[0030] When the other resin is contained, a polyolefin resin or an acrylic resin is preferable. The acrylic resin may be either an acrylic acid resin or a polyacrylic acid ester, but an acrylic acid resin is more preferable.

[0031] Examples of polyolefin resins include polyethylene and polypropylene, which are preferred from the viewpoint of making the corrosion-resistant coating layer flexible and reducing defects such as cracks, etc. Also, acrylic resins are preferred from the viewpoint of forming interactions such as hydrogen bonds and crosslinks with the hydrophilic coating layer and increasing the adhesion between the coatings.

[0032] The epoxy resin and other resins in this embodiment may be linear or crosslinked. In the case of crosslinking, for example, in the case of an acrylic resin, crosslinking may be performed by dehydration condensation caused by baking during film formation, etc. Crosslinking by dehydration condensation may be performed via polyols such as carboxymethyl cellulose, polyvinyl alcohol, and polyethylene oxide.

[0033] In addition, when crosslinked, it may be crosslinked with a crosslinking agent. Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, an oxazoline-based crosslinking agent, a carbodiimide-based crosslinking agent, and an aziridine-based crosslinking agent.

[0034] In addition to the above, the corrosion-resistant coating layer in this embodiment may contain other optional components within the range that does not impair the effects of the present invention. Examples of optional components include various paint additives for improving the physical properties of the coating. Examples of paint additives include crosslinkers, surfactants, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, rust inhibitors, and antibacterial agents. Among these, it is preferable to include an antibacterial agent. These paint additives may be included in one type or in two or more types.

[0035] The amount of the corrosion-resistant coating layer is 0.1 to 20 mg / dm 2 From the viewpoint of good corrosion resistance and adhesion between layers, the coating amount is preferably 0.1 mg / dm 2 More than 1.0 mg / dm 2 More preferably, 1.5 mg / dm 2 On the other hand, from the viewpoints of good film-forming property, reduction of defects such as cracks, keeping the heat transfer resistance of the film low, suppressing the inhibition of the heat exchange efficiency of the fin material, and not inhibiting the functions of other film layers, the above-mentioned film amount is 20 mg / dm 2 Less than 18 mg / dm 2 Less than 15 mg / dm is more preferable. 2 The following is even more preferred:

[0036] The coating weight of the corrosion-resistant coating layer can be adjusted by the concentration of the coating composition used to form the corrosion-resistant coating layer, the selection of the bar coater number used to form the coating, etc. The coating weight of the corrosion-resistant coating layer can be measured by known methods such as fluorescent X-rays, an infrared coating thickness meter, and weight measurement by coating peeling.

[0037] <Hydrophilic film layer> The hydrophilic coating layer is a coating layer that imparts hydrophilicity to the surface of the fin material, and contains a conventionally known hydrophilic resin.

[0038] The hydrophilic resin may contain one type of resin or two or more types of resins as long as it has a hydrophilic group. Examples of the hydrophilic group include a hydroxyl group, a carboxyl group, a sulfonic acid group, and a polyether group.

[0039] Examples of hydrophilic resins having a hydroxyl group include polyethylene glycol (PEG) and polyvinyl alcohol (PVA). An example of a hydrophilic resin having a carboxyl group is polyacrylic acid (PAA). An example of a hydrophilic resin having a hydroxyl group and a carboxyl group is carboxymethyl cellulose (CMC). An example of a hydrophilic resin having a sulfonic acid group is sulfoethyl acrylate. Examples of hydrophilic resins having a polyether group include polyethylene glycol (PEG) and modified compounds thereof.

[0040] Among these, from the viewpoint of more suitably expressing the desired hydrophilicity even when a lubricating coating layer is formed on the surface of the hydrophilic coating layer, the hydrophilic resin is preferably one containing a sulfonic acid group or a polyether group, i.e., one containing an ether bond, more preferably one containing a sulfonic acid group and an ether bond, and particularly preferably an acrylic acid resin containing a sulfonic acid group and an ether bond.

[0041] The acrylic acid resin containing sulfonic acid and ether bonds is an acrylic acid resin containing an unsaturated double bond group and a sulfonic acid group, and is typically 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium salt (HAPS), but other examples include acrylamidomethylpropanesulfonic acid, etc. The acrylic acid resin containing sulfonic acid and ether bonds is not limited to these.

[0042] In addition to the above, the hydrophilic resin may be a copolymer of two or more monomers having a hydrophilic group. For example, a copolymer of acrylic acid and sulfoethyl acrylate may be used. The copolymer may be an alternating copolymer, a block copolymer, a graft copolymer, a random copolymer, or the like, and the arrangement of the monomers is not particularly limited.

[0043] The hydrophilic coating layer preferably contains a surfactant in addition to the hydrophilic resin. In this way, when a lubricating coating layer is formed on the hydrophilic coating layer, the lubricating coating layer can provide both good processability and good hydrophilicity. This is believed to be due to the exposure effect of the surfactant.

[0044] The surfactant may be any of anionic, cationic, and nonionic surfactants, but anionic surfactants are preferred from the viewpoint of ease of dispersion in the hydrophilic coating layer. One type of surfactant may be used, or two or more types may be used in combination.

[0045] Examples of the anionic surfactant include polyoxyethylene alkyl ether phosphate, polyoxyethylene alkyl ether sulfate, and polyoxyethylene alkyl sulfosuccinate.

[0046] Examples of nonionic surfactants include ethylenediamine polyoxypropylene-polyoxyethylene condensates, polyoxyethylene sorbitan monolaurate, polyoxyethylene polyoxypropylene block polymers, polyoxyethylene sorbitan monostearate, and the like.

[0047] In addition to the hydrophilic resin and surfactant, the hydrophilic coating layer may contain other optional components within the range that does not impair the effects of the present invention. Examples of the optional components include various paint additives for improving the physical properties of the coating layer. Examples of paint additives include crosslinking agents, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, rust inhibitors, antibacterial agents, antifungal agents, etc. These paint additives may be contained alone or in combination of two or more.

[0048] The coating amount of the hydrophilic coating layer in this embodiment is 0.1 to 28 mg / dm 2 Here, from the viewpoint of obtaining better hydrophilicity, the coating amount of the hydrophilic coating layer is preferably 0.1 mg / dm 2 More than 0.3 mg / dm 2 More preferably, 0.5 mg / dm 2 More preferably, the amount of the hydrophilic coating layer is 28 mg / dm2 or more, from the viewpoint of obtaining good coating workability when forming the hydrophilic coating layer, and from the viewpoint of obtaining good functions of the corrosion-resistant coating layer formed on the aluminum plate side of the hydrophilic coating layer. 2 Less than 25 mg / dm 2 The following is more preferred:

[0049] The amount of hydrophilic resin attached to the hydrophilic coating layer is 0.05 to 5 g / m 2 Here, from the viewpoint of obtaining sufficient hydrophilicity, the coating amount is preferably 0.05 g / m 2 More than 0.1 g / m is preferable. 2 More preferably, 0.3 g / m or more 2 The above-mentioned adhesion amount is more preferably 5 g / m from the viewpoint of preventing the hydrophilic resin from eluting when the surface of the fin material becomes wet with water and impairing the oil repellency of the functional film. 2 Less than 1 g / m is preferable. 2 Less than 0.8 g / m is more preferable. 2 The following is even more preferred:

[0050] When the hydrophilic film contains a surfactant, the amount of the surfactant attached to the hydrophilic film is 0.0003 to 0.7 g / m 2 Here, from the viewpoint of obtaining sufficient hydrophilicity, the adhesion amount is preferably 0.0003 g / m 2 More than 0.0005 g / m is preferable. 2 More preferably, 0.001 g / m or more 2 In addition, in the case where the hydrophilicity is too strong and a lubricating coating layer is provided on the hydrophilic coating layer, the coating amount is preferably 0.7 g / m from the viewpoint of preventing the lubricity of the lubricating coating layer from being hindered. 2 Less than 0.5 g / m is preferred. 2 Less than 0.05 g / m is more preferable. 2 The following is even more preferred:

[0051] The coating weight of the hydrophilic coating layer can be adjusted by the concentration of the coating composition used to form the hydrophilic coating layer, the selection of the bar coater number, and the like.

[0052] <Lubricating film layer> The aluminum fin material according to this embodiment preferably further comprises a lubricating coating layer on the surface of the hydrophilic coating layer. The lubricating coating layer is more preferably the outermost layer of the aluminum fin material.

[0053] The lubricating coating layer is a layer that enhances the lubricity of the fin material surface. This reduces the friction coefficient of the fin material and improves processability, such as press formability, when the fin material is processed into a fin.

[0054] The lubricating coating layer in this embodiment preferably contains a resin matrix and a hydrophilic component. Here, the resin matrix means a resin component that is a base composition for forming the lubricating coating layer. The content of the resin matrix is ​​preferably 60% by mass or more based on the total amount of components constituting the lubricating coating layer. In addition, from the viewpoint of fully exerting the functions of the components other than the resin matrix, the content is preferably 70% by mass or less.

[0055] The resin matrix in this embodiment preferably contains polyethylene glycol (PEG) as a main component, from the viewpoint of suppressing deterioration of hydrophilic function due to heat and obtaining good heat resistance when combined with a specific hydrophilic component described later. Here, the main component of the resin matrix means that the content thereof is 60 mass % or more with respect to the total resins constituting the resin matrix.

[0056] The polyethylene glycol mentioned above also includes modified compounds thereof. The modified polyethylene glycol compound may be a modified polyethylene glycol having in its structure a functional group having one or more bonds selected from the group consisting of a urethane bond, an ester bond, and an ether bond. Among these, a modified polyethylene glycol having in its structure a functional group having a urethane bond is preferred in terms of having a functional group with excellent elongation.

[0057] Furthermore, when the resin matrix contains two or more types of polyethylene glycols with different molecular weights or structures, if the total amount of these is 60 mass % or more, it can be said that the resin matrix contains polyethylene glycol as a main component.

[0058] In the resin matrix of this embodiment, the content of polyethylene glycol, which is the main component, is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and may be 100% by mass, i.e., the resin matrix may consist only of polyethylene glycol.

[0059] In the case where the resin matrix in this embodiment contains a resin other than polyethylene glycol, the other resin may be, for example, a resin having a hydrophilic group, such as a hydroxyl group, a carboxyl group, a sulfonic acid group, or a polyether group.

[0060] Examples of resins having a hydroxyl group other than polyethylene glycol (PEG) include polyvinyl alcohol (PVA). An example of a material having a carboxyl group is polyacrylic acid (PAA). An example of a material having a hydroxyl group and a carboxyl group is carboxymethyl cellulose (CMC). An example of a compound having a sulfonic acid group is sulfoethyl acrylate. In addition to these, copolymers of two or more kinds of monomers having a hydrophilic group can also be used.

[0061] The hydrophilic component in this embodiment is preferably a component containing at least one of a sulfonic acid group and an ester group, and more preferably one in which the amount of functional groups contributing to hydrophilicity changes by 15% or less before and after heating for 10 minutes at 200° C. This allows the hydrophilic effect of the hydrophilic coating layer to be maintained without being lost due to heating or the like, and realizes hydrophilicity with excellent heat resistance.

[0062] Examples of hydrophilic components containing at least one of a sulfonic acid group and an ester group include sulfonic acid acrylic compounds, phosphate ester compounds, acrylic compounds, etc. It is more preferable that these compounds have a change in the amount of functional groups that contribute to hydrophilicity of 15% or less before and after heating at 200° C. for 10 minutes.

[0063] The change in the amount of functional groups that contribute to hydrophilicity of the hydrophilic component before and after heating at 200° C. for 10 minutes is preferably 15% or less, more preferably 10% or less, and even more preferably 5% or less. In this specification, the change in the amount of functional groups that contribute to hydrophilicity can be measured using a Fourier transform infrared spectrophotometer.

[0064] In this embodiment, the content of the hydrophilic component relative to 100 parts by mass of the resin matrix is ​​preferably 2.0 to 6000 parts by mass. From the viewpoint of obtaining high hydrophilicity, the content is preferably 2.0 parts by mass or more, more preferably 5.0 parts by mass or more, even more preferably 6.0 parts by mass or more, even more preferably 8.0 parts by mass or more, and particularly preferably 10 parts by mass or more. On the other hand, from the viewpoint of obtaining good processability, the content is preferably 6000 parts by mass or less, more preferably 5000 parts by mass or less, even more preferably 4000 parts by mass or less, and particularly preferably 3000 parts by mass or less. In this way, by setting the content of the hydrophilic component in the resin matrix within an appropriate range, it is possible to achieve and improve both good processability and properties such as hydrophilicity related to prevention of water splashing and reduction of ventilation resistance without interfering with each other.

[0065] In addition to the resin matrix and the hydrophilic component, the lubricating coating layer in this embodiment may contain other optional components within the scope of the present invention, such as various paint additives for improving the physical properties of the coating layer. Examples of paint additives include crosslinkers, surfactants, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, antifouling agents, rust inhibitors, antibacterial agents, antifungal agents, etc. These paint additives may be contained alone or in combination of two or more.

[0066] The coating amount of the corrosion-resistant coating layer in this embodiment is 0.05 to 3.0 mg / dm 2 Here, from the viewpoint of obtaining sufficient corrosion resistance and heat-resistant hydrophilicity, the coating amount is preferably 0.05 mg / dm 2 More than 0.1 mg / dm 2 More preferably, 0.2 mg / dm 2 On the other hand, from the viewpoint of suppressing a decrease in hydrophilicity due to a part of the components constituting the lubricating coating layer remaining on the surface when the surface of the fin material is wetted with water, the above coating amount is 3.0 mg / dm 2 Less than 1.5 mg / dm 2 Less than 1.0 mg / dm is more preferable.2 The following is even more preferred:

[0067] The coating weight of the corrosion-resistant coating layer can be adjusted by the concentration of the coating composition used to form the corrosion-resistant coating layer, the selection of the bar coater number, and the like.

[0068] In the aluminum fin material according to this embodiment, the total thickness of the corrosion-resistant coating layer, the hydrophilic coating layer, and the lubricating coating layer is preferably 5 μm or less in order to prevent a decrease in the heat exchange efficiency of the fin material.

[0069] <Aluminum plate> The aluminum plate in this embodiment is a concept that includes a plate made of aluminum and a plate made of an aluminum alloy, and an aluminum plate that has conventionally been used for aluminum fin materials can be used.

[0070] As the aluminum plate, 1000 series aluminum as specified in JIS H 4000:2014 is preferable because of its excellent thermal conductivity and workability. More specifically, aluminum alloy numbers 1050, 1070, and 1200 are more preferable as the aluminum plate. However, the above description does not exclude the use of 2000 series to 9000 series aluminum alloys or other aluminum plates as the aluminum plate.

[0071] The aluminum plate is cut to a desired thickness depending on the application and specifications of the fin material. The fin material for heat exchangers preferably has a thickness of 0.08 to 0.3 mm. From the viewpoint of the strength of the fin, the thickness of the fin material is preferably 0.08 mm or more, and more preferably 0.1 mm or more. On the other hand, from the viewpoint of the workability into the fin and the heat exchange efficiency, the thickness of the fin material is preferably 0.3 mm or less, and more preferably 0.2 mm or less.

[0072] At least a corrosion-resistant coating layer and a hydrophilic coating layer are provided in this order on at least one surface of the aluminum plate, but at least a corrosion-resistant coating layer and a hydrophilic coating layer may be provided in this order on both surfaces. In addition, when a corrosion-resistant coating layer and a hydrophilic coating layer are provided on both surfaces, the configurations of the coating layers on both surfaces do not necessarily have to be the same.

[0073] <Base treatment layer> The aluminum fin material according to this embodiment may further include a base treatment layer between the aluminum plate and the corrosion-resistant coating layer. By providing the undercoat treatment layer, the corrosion resistance of the aluminum plate can be improved, and also the adhesion between the aluminum plate and the corrosion-resistant coating layer can be improved.

[0074] The undercoat treatment layer in this embodiment may be any known layer that can impart corrosion resistance to the aluminum plate, such as a layer made of an inorganic oxide or an inorganic-organic composite compound. Examples of inorganic materials that form inorganic oxides and inorganic-organic composite compounds include chromium (Cr), zirconium (Zr), and titanium (Ti).

[0075] The layer made of an inorganic oxide that serves as the undercoat treatment layer can be formed, for example, by subjecting an aluminum plate to a chromate phosphate treatment, a zirconium phosphate treatment, a zirconium oxide treatment, a chromate chromate treatment, a zinc phosphate treatment, a titanic acid phosphate treatment, etc. However, the type of inorganic oxide is not limited to those formed by these treatments.

[0076] The layer made of an inorganic-organic composite compound that serves as the undercoat treatment layer can be formed, for example, by subjecting an aluminum plate to coating-type chromate treatment, coating-type zirconium treatment, etc. Specific examples of such inorganic-organic composite compounds include, for example, acrylic-zirconium composites.

[0077] The thickness of the undercoat treatment layer is not particularly limited and may be set appropriately, but the amount of the coating per unit area should be 1 to 100 mg / m2 in terms of metal (Cr, Zr, Ti). 2 The thickness of the film is preferably 1 to 100 nm.

[0078] The coating amount and film thickness of the undercoat treatment layer can be adjusted by the concentration of the chemical conversion treatment solution used in forming the undercoat treatment layer, the film formation treatment time, and the like.

[0079] <Characteristics of aluminum fin material> The aluminum fin material according to this embodiment has extremely excellent corrosion resistance. If aluminum fin material has low corrosion resistance, it is easy for the aluminum to produce corrosion products. The aluminum corrosion products are accompanied by an odor called a corrosion odor. Therefore, if the fin material has no odor at all or only a slight odor is detected after undergoing a moisture resistance test by the method described in the examples below, it can be evaluated as having very excellent corrosion resistance.

[0080] Furthermore, when considering that the aluminum fin material is to be used in, for example, a heat exchanger, it is necessary for the aluminum fin material to have hydrophilicity at least equal to that of conventional materials. Specifically, if the contact angle of a droplet measured by the method described in the Examples below is 45° or less, it can be evaluated as having good hydrophilicity at least equal to that of conventional materials, and the contact angle is more preferably 40° or less, even more preferably 30° or less, and particularly preferably 20° or less.

[0081] <<Method for manufacturing aluminum fin material>> The aluminum fin material obtained by the manufacturing method according to the present embodiment includes an aluminum plate, and a corrosion-resistant coating layer and a hydrophilic coating layer, in this order, on at least one surface of the aluminum plate. The manufacturing method includes a step of applying and dehydrating and condensing a coating composition containing an epoxy resin composition and at least one of silicone and a silane coupling agent having an epoxy group to form the corrosion-resistant coating layer.

[0082] The manufacturing method according to this embodiment can manufacture the fin material described in the above "Aluminum Fin Material", but the fin material may also be manufactured by other manufacturing methods.

[0083] The manufacturing method according to this embodiment will be specifically described below. In the following, a base treatment layer, a corrosion-resistant film layer, a hydrophilic film layer, and a lubricant film layer are formed on the surface of an aluminum plate in this order, but the formation of the base treatment layer and the lubricant film layer is optional. In addition, a film layer having another function may be further provided.

[0084] When forming a base treatment layer on the surface of an aluminum plate, a conventionally known method can be adopted. Specifically, when the base treatment layer is a layer made of an inorganic oxide, for example, the base treatment layer can be formed by subjecting the aluminum plate to a chromate phosphate treatment, a zirconium phosphate treatment, a zirconium oxide treatment, a chromate chromate treatment, a zinc phosphate treatment, a titanic acid phosphate treatment, or the like. When the undercoat treatment layer is a layer made of an inorganic-organic composite compound, the undercoat treatment layer can be formed, for example, by subjecting the aluminum plate to a coating type chromate treatment or a coating type zirconium treatment.

[0085] Before forming the primer layer, the surface of the aluminum plate may be degreased in advance using an alkaline degreasing solution, which improves the reactivity of the primer treatment and also improves the adhesion of the formed primer layer.

[0086] Next, in the step of forming a corrosion-resistant coating layer, a coating composition containing an epoxy resin composition and at least one of silicone and a silane coupling agent having an epoxy group is applied and subjected to dehydration condensation. Through dehydration condensation, at least one of the silicone and the silane coupling agent, both of which have an epoxy group, becomes a silicone having an epoxy group, and a corrosion-resistant coating layer containing an epoxy resin and a silicone containing an epoxy group is formed.

[0087] The above coating composition may further contain an alcohol-based solvent, an ether-based solvent, the above-mentioned coating additives, etc., from the viewpoint of improving the coating properties, workability, physical properties of the coating, etc.

[0088] In the step of forming the corrosion-resistant coating layer, drying may be carried out as necessary after the above-mentioned dehydration condensation.

[0089] The hydrophilic coating layer can be formed by applying a coating composition containing a hydrophilic resin and, if necessary, a surfactant onto the corrosion-resistant coating layer, and then solidifying the composition by drying or the like. The above coating composition may further contain an aqueous solvent, a water-soluble organic solvent, the above-mentioned coating additives, etc., from the viewpoint of improving the coatability, workability, physical properties of the coating, etc.

[0090] The lubricating coating layer can be formed by applying a coating composition containing a resin that enhances lubricity, for example a coating composition containing a resin matrix and a hydrophilic component, onto the hydrophilic coating layer and solidifying it by drying or the like. The above coating composition may further contain an aqueous solvent, a water-soluble organic solvent, the above-mentioned coating additives, etc., from the viewpoint of improving the coatability, workability, physical properties of the coating, etc.

[0091] The solidification may be performed by baking. The baking temperature is not particularly limited as long as the lubricating coating layer does not peel off, but is preferably, for example, 100 to 250° C. Here, the above temperature is preferably 100° C. or higher, and more preferably 150° C. or higher. Moreover, from the viewpoint of preventing oxidation of the resin of the lubricating coating layer, the above temperature is preferably 250° C. or lower, and more preferably 200° C. or lower. The above baking temperature is the temperature of the oven in which baking is performed.

[0092] The baking time is not particularly limited as long as the lubricating coating layer does not peel off, but is preferably, for example, 3 to 30 seconds. Here, the time is preferably 3 seconds or more, more preferably 5 seconds or more. Moreover, from the viewpoint of preventing oxidation of the resin of the lubricating coating layer, the time is preferably 30 seconds or less, more preferably 20 seconds or less. EXAMPLES

[0093] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples, and can be practiced with modifications within the scope of the invention, all of which are included in the technical scope of the present invention.

[0094] Examples 1 to 13, Comparative Examples 1 to 19, and Reference Example 1 The aluminum plate used was an aluminum plate having a thickness of 0.1 mm and conforming to the alloy number 1070 standard specified in JIS H 4000: 2014. A primer layer was formed on one surface of the aluminum plate by phosphate chromate treatment.

[0095] Next, a coating composition was prepared by dispersing an epoxy resin composition (EPICLON (registered trademark) 840, manufactured by DIC Corporation) in water, and this was applied to the surface of the base treatment layer using a bar coater so as to obtain the coating amount shown in Table 1. After dehydration condensation was carried out at 200°C for 15 seconds, the coating was dried to form a corrosion-resistant coating layer.

[0096] In addition, the above coating composition was added with a predetermined amount of silicone precursors, such as epoxy group-containing silicone emulsion in Examples 1 to 4 and Examples 11 to 13, epoxy group-containing silicone A in Examples 5 and 6, epoxy group-containing silicone B in Examples 7 and 8, epoxy group-containing silane coupling agent in Examples 9 and 10, epoxy group-free silicone A in Comparative Examples 3 and 4, and epoxy group-free silicone B in Comparative Examples 5 and 6, so that the content of silicone obtained was the value shown in Table 1 or 2. Here, the epoxy group-containing silicone A and the epoxy group-containing silicone B have different amounts of epoxy functional groups, and the amount of epoxy functional groups in the epoxy group-containing silicone A is about twice as much per mol as the epoxy group-containing silicone B. In addition, the epoxy group-free silicone A and the silicone B have different amounts of functional groups, and the amount of functional groups in the epoxy group-free silicone A is about twice as much per mol as the epoxy group-free silicone B. In addition, in Comparative Examples 1, 2, and 7 to 19 and Reference Example 1, no silicon or silane coupling agent was added to the coating composition.

[0097] Next, a coating composition was prepared by dispersing an acrylic acid resin containing a sulfonic acid group and an ether bond in water, and the coating amount was set to 3 mg / dm 2 The coating was applied to the surface of the corrosion-resistant coating layer using a bar coater so that the coating had a hydrophilic property. The coating was then subjected to dehydration and condensation at 200° C. for 15 seconds, and then dried to form a hydrophilic coating layer.

[0098] In addition, the above coating composition was added with a predetermined amount of epoxy group-containing silicone emulsion in Comparative Examples 7 to 9, epoxy group-containing silicone A in Comparative Examples 10 and 11, epoxy group-containing silicone B in Comparative Examples 12 and 13, epoxy group-containing silane coupling agent in Comparative Examples 14 and 15, epoxy group-free silicone A in Comparative Examples 16 and 17, and epoxy group-free silicone B in Comparative Examples 18 and 19, so that the content of the silicone obtained was the value shown in Table 1 or 2. Here, the epoxy group-containing silicone A and the epoxy group-containing silicone B have different amounts of epoxy functional groups, and the amount of epoxy functional groups in the epoxy group-containing silicone A is about twice as much per mol as the epoxy group-containing silicone B. In addition, the epoxy group-free silicone A and the silicone B have different amounts of functional groups, and the amount of functional groups in the epoxy group-free silicone A is about twice as much per mol as the epoxy group-free silicone B.

[0099] Finally, a coating composition was prepared by dispersing polyethylene glycol (PEG6000, manufactured by Sanyo Chemical Industries, Ltd.) in water, and the coating amount was set to 0.2 mg / dm 2 The lubricating coating layer was formed by applying the lubricating agent to the surface of the hydrophilic coating layer using a bar coater so as to obtain a coating having a lubricating effect. The coating was then baked at 150° C. for 15 seconds to form a lubricating coating layer. In this manner, an aluminum fin material was obtained.

[0100] "evaluation" <Hydrophilicity> The fin material was immersed in a water tank filled with tap water for 8 hours, and then dried at 80°C for 16 hours, which constituted one cycle. This immersion and drying process was repeated five times. After that, the temperature was returned to room temperature, and about 2 μL of ion-exchanged water was dropped onto the fin material surface, and the contact angle of the droplet was measured with a contact angle measuring device (Kyowa Interface Science Co., Ltd.: CA-05 type). The contact angle was measured three times for each sample, and the average value was taken as the contact angle. The results are shown in the "hydrophilicity" section of Table 1. A contact angle of 45° or less can be evaluated as having good hydrophilicity equal to or better than that of conventional contact angles, and a contact angle of 40° or less is more preferable. The smaller the contact angle, the higher the hydrophilicity.

[0101] <Corrosion resistance> A moisture resistance test was conducted by placing the fin material in an atmosphere of 40°C and a humidity of 98% or more for 500 hours. The odor intensity of the fin material was evaluated 300 hours and 500 hours after the start of the moisture resistance test. The evaluation criteria were as follows, and if the evaluation was 0 to 2 both 300 hours and 500 hours after the start of the moisture resistance test, the corrosion resistance was judged to be very good. The results are shown in "Corrosion Resistance" in Table 1. 0: No odor is detected at all. 1: A slight odor is detected, but it is not clear what the odor is (detection threshold). 2: A faint odor can be detected and the odor can be determined (cognitive threshold). 3: The odor is strong and it is easy to determine what it is. 4: The odor is very strong and some types of odor are unpleasant.

[0102] [Table 1]

[0103] [Table 2]

[0104] The results in Tables 1 and 2 show that by including epoxy group-containing silicone in the corrosion-resistant coating layer, very good corrosion resistance can be achieved. On the other hand, as can be seen from the results of Comparative Examples 3 to 6, even if the corrosion-resistant coating layer contains silicone, if the silicone does not contain epoxy groups, the corrosion resistance is about the same as that of Comparative Example 1. Simply adding silicone to the corrosion-resistant coating layer does not improve the corrosion resistance.

[0105] Furthermore, the results of Comparative Examples 7 to 15 showed that even if the epoxy group-containing silicone was incorporated into the hydrophilic coating layer rather than the corrosion-resistant coating layer, not only was no improvement in corrosion resistance observed, but the hydrophilic effect of the hydrophilic coating layer was also inhibited.

[0106] Furthermore, from the results in Table 2, in the case of a corrosion-resistant coating layer that does not contain silicone containing epoxy groups, as shown in Reference Example 1, the coating amount is 25 mg / dm 2 In contrast, a corrosion-resistant coating layer containing silicone containing epoxy groups can achieve the same corrosion resistance with a smaller amount of coating. As described above, the corrosion-resistant coating layer in this embodiment has excellent corrosion resistance, so that the amount of coating can be reduced, which is advantageous from the viewpoint of manufacturing costs.

Claims

1. An aluminum plate having a corrosion-resistant coating layer and a hydrophilic coating layer in this order on at least one surface of the aluminum plate; The aluminum fin material, wherein the corrosion-resistant coating layer contains an epoxy resin and a silicone containing an epoxy group.

2. The aluminum fin material according to claim 1, wherein the content of the epoxy group-containing silicone in the corrosion-resistant coating layer is 0.1 to 20 mass%.

3. The coating amount of the corrosion-resistant coating layer is 0.1 to 20 mg / dm 2 The aluminum fin material according to claim 1 or 2.

4. The aluminum fin material according to claim 1 or 2, wherein the hydrophilic coating layer comprises an acrylic resin containing a sulfonic acid group and an ether bond.

5. The aluminum fin material according to claim 1 or 2, further comprising a lubricating coating layer on a surface of the hydrophilic coating layer.

6. The aluminum fin material according to claim 5, wherein the lubricating coating layer comprises a resin matrix containing polyethylene glycol as a main component and a hydrophilic component containing at least one of a sulfonic acid group and an ester group.

7. The aluminum fin material according to claim 1 or 2, further comprising a base treatment layer between the aluminum plate and the corrosion-resistant coating layer.

8. A method for manufacturing an aluminum fin material comprising an aluminum plate and a corrosion-resistant coating layer and a hydrophilic coating layer in this order on at least one surface of the aluminum plate, A method for producing an aluminum fin material, comprising the steps of applying and dehydrating and condensing a coating composition containing an epoxy resin composition and at least one of silicon and a silane coupling agent having an epoxy group, to form the corrosion-resistant coating layer.

Citation Information

Patent Citations

  • High-temperature-resistant corrosion-resistant coating material for sulfur-containing heat exchanger, and preparation method thereof, and corrosion-resistant shell-and-tube heat exchanger

    CN114075402A

  • Organic composite coated steel sheet

    JP2007138248A

  • Heat exchanger and air conditioner or clothing washer-dryer using the same

    JP2011002146A

  • Bilayer coated film formation method

    JP2020192516A

  • Aluminum fin material

    JP2022161706A